Locational distribution of health care facilities in the rural area of Ondo State (2015)
"Aim: This research is aimed to assess the locational Distribution of health care facilities in the rural area of Ondo state. Study Design: Case study research design. Place and Duration of Study: Three senatorial districts of Ondo state Nigeria and lies within latitude 50 451 and 70521 N and longitude 40 201 and 60 51 E between July 2010 and September 2011. Methodology: This study was conducted within 3 senatorial districts in the study area. The Global Positioning System (GPS) was adopted to take the coordinate of all the existing health care facilities in the area. “Nearest Neighbour Analysis” (NNA) was the inferential statistical used in analyzing the data. This was used in establishing the distribution pattern of health facilities in the study area. Nearest Neighbour Analysis is the method of exploring pattern in the locational data by comparing mean distance (Do) of the phenomena in question to the same expected mean distance (De) usually under a random distribution of any phenomenon. Results: The distribution of health care facilities in the area was clustered with the z-score table value for the three senatorial districts (Akure North, Ilaje and Ose) as 18.74, 35.31 and 21.44 respectively. This result does not enjoy adequate randomization thereby having implication for effective planning. Conclusion: Results from the study show that health care facilities in the state were unevenly distributed, hence hampering health development at the grassroots. In the area where population is not evenly distributed, the mean centre of population distribution is calculated as the “demand”, which forms the origin of location. The facility location point is considered as destination points or “supply”. The study suggests proper planning through the location of more and adequately equipped medical facilities in the rural area of Ondo state so as to enhance sustainable health care delivery."